2011
DOI: 10.5430/jms.v2n3p21
|View full text |Cite
|
Sign up to set email alerts
|

Perception: A Guide for Managers and Leaders

Abstract: Managers and leaders in organization are entrusted with employees whom they must work with and through to realize organizational objectives. In organizations, perceptions of leaders, managers and employees shape the climate and effectiveness of the working environment. Perception is the way we all interpret our experiences. Having the right perception is significant skill for any effective leadership. It is important to understand that perception is often portrayed through communication in any organization be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 2 publications
4
23
0
1
Order By: Relevance
“…We analysed students' perceptions of management in order to explain students' understanding and valuation about the business environment in which they live and (will one day) work (Aktepebasi et al, 2018). The way students see different stakeholders, such as bosses, leaders, managers, and employees have an important role in determining overall effectiveness of the working environment (Otara, 2011). Interesting finding in our analysis is the perception of contemporary students of management; the way they perceive management is mainly functions-based view, which is in line with the mainstream management theory of the 21 st century.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We analysed students' perceptions of management in order to explain students' understanding and valuation about the business environment in which they live and (will one day) work (Aktepebasi et al, 2018). The way students see different stakeholders, such as bosses, leaders, managers, and employees have an important role in determining overall effectiveness of the working environment (Otara, 2011). Interesting finding in our analysis is the perception of contemporary students of management; the way they perceive management is mainly functions-based view, which is in line with the mainstream management theory of the 21 st century.…”
Section: Discussionmentioning
confidence: 99%
“…Perception is also an individual's sensory experience of the environment in which he or she lives and is at the same time focused on the recognition of environmental stimuli and typical actions that are a response to such stimuli. Moreover Otara (2011) proposed that managing perceptions in the process of dealing with employees and organizational challenges is typically what distinguishes great from average leaders. Elsbach (2003) suggested that the topic of organizational perception management has its roots way back in history from the times of ancient Greece.…”
Section: Theoretical Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In today's modern business environment all managers are required to provide leadership to employees (Otara, 2011). Leadership allows organisations to achieve change and growth while management allows organisations to achieve order, stability and consistency.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Management also relies on the acquisition, distribution and utilization of the current resources and structures. Leadership on the other hand is responsible for designing new resources and opportunities for the future (Otara, 2011). Finally, both leadership and management deal with human resource management, however, management tends to be tactical to achieve success in the day to day performance of employees.…”
Section: Literature Reviewmentioning
confidence: 99%